Control de la enfermedad Roya Asiática de la Soya (Phakopsora pachyrhizi) en el cultivo de soya en la zona de Babahoyo Provincia de Los Ríos - Mora Vargas, Ángel Tomas (2019)
SUMMARY CONTROL OF RUST DISEASE ASIAN SOY (PHAKOPSORA PACHYRHIZI) IN THE CULTIVATION OF SOY IN THE AREA OF BABAHOYO RIVERS PROVINCE AUTHOR: Ángel Tomas Mora Vargas TUTOR: Mg. Ing. Agric. Yari Ruiz Parrales MAE. The exploitation of soybean after rice and maize is one of the short-cycle crops of major importance in the Ecuadorian coast. In the province of Los Rios are planted during the dry period, more than 50,000 ha, yields ranging from 1000-1800 kg / ha, a variation that is due to the use of technology developed by the crop. The soybean rust is a disease caused by the fungus Phakopsora pachyrhizi ) , with large numbers of primary hosts including soybeans ( Glycine max ) , wild soybean (G. sojae ) , habilla ( Pachyrhizus erosus ) , beans or bean ( Phaseolus vulgaris) . Severe infection of the pathogen reduction performance therefore affects the producer financially. The treatments were arranged in a complete block design random. At the end of the crop cycle were evaluated: plant height, days to flowering, loading height, and number of pods per plant, number of grains per pod, yield per hectare, incidence and severity of disease. For the evaluation of means used the Tukey test at 5 % significance. Keywords: short cycle crops, disease, hosts, yield.